Investigasi Forensik Email dengan Berbagai Pendekatan dan Tools - Zefanya Deianera Anabelle; Mustari Lamada; Satria Gunawan Zain (Progressive Information, Security, Computer, and Embedded System, 2024)
Email  forensic investigation is one of the important areas in digital forensics that aims to uncover digital evidence through email  analysis. This study discusses various approaches and tools used in email  forensic investigations, with a focus on identifying and tracking suspicious activity, metadata analysis, and conversation reconstruction. The methods applied include header analysis, email  authentication checks, and the use of anomaly detection algorithms. The tools used in the study included open-source and commercial software designed specifically for digital forensics, such as EnCase, FTK, and Mail Xaminer. The case studies presented demonstrate the effectiveness of these various approaches and tools in detecting cybercrimes such as phishing, fraud, and the spread of malware via email . The results of this study provide practical guidance for forensic investigators in choosing the right approach and tools according to the characteristics of the case being handled, and emphasize the importance of an in-depth understanding of the structure and mechanism of email s to obtain accurate and accountable results in court.